HUBUNGAN METODE PEMBELAJARAN DARING DI MASA PANDEMI COVID-19 DENGAN TINGKAT STRESS MAHASISWA - Nonny Yulia Sabrina; Cecep Heriana; Nanang Saprudin (Lembaga Penelitian & Pengabdian Masyarakat Sekolah Tinggi Ilmu KesehatanBrebes, 2021)
Background: Changes in Learning Methods to Online in the Covid-19 Pandemic Period experienced several obstacles including inadequate networks, more lecture assignments resulting in students experiencing Stress Levels. The purpose of this study was to determine the relationship between online learning methods during the COVID-19 pandemic and the stress level of S1 Nursing students at the Institute Of Health Sciences Kuningan in 2021. Methods: This type of research uses descriptive analytic with cross sectional design. The study population was 573 with a research sample of 220. The sample technique used proportionate stratified random sampling. The analysis was performed with univariate and bivariate using chi-square test. Results: Less effective online learning methods are 126 (57.3%) with moderate stress levels as much as 92 (41.8%) and effective online learning methods as many as 94 (42.7%) with mild stress levels as much as 84 (38.2 %). For bivariate results, the p value = 0.002. There is a relationship between online learning methods during the covid-19 pandemic and the stress level of S1 Nursing students at the Institute Of Health Sciences Kuningan in 2021. Conclusions: Become an evaluation material for institutions so that learning methods are more interesting and not boring, such as the ability to use technology by playing videos of learning materials. Also, uniting perception and concentration so that students can easily adapt and understand the material easily.